PENGARUH SISTEM INFORMASI PENGELOLAAN KEUANGAN DAERAH (SIPKD), PENGENDALIAN INTERN, KOMPETENSI SUMBER DAYA MANUSIA DAN GOOD GOVERNANCE TERHADAP KUALITAS LAPORAN KEUANGAN DAERAH - Khairunnas Khairunnas; Teguh Erawati; Anita Primastiwi (INVOICE : JURNAL ILMU AKUNTANSI, 2021)
This study aims to examine whether the local financial management information system, internal control, human resource competence and good governance on the quality of regional financial reports at OPD Bima City. This research method uses descriptive qualitative and primary methods using questionnaires. The study took a sample of 60 employees in the Bima City OPD. The data collection technique used purposive sampling technique. Data collection was carried out by distributing questionnaires in the form of a google form questionnaire which was distributed to Bima City OPD employees. The number of questionnaires that were processed were 60 questionnaires. Data were analyzed using multiple linear regression analysis.                The results of this study indicate that the regional financial management information system (sipkd), internal control and human resource competence have a negative effect on the quality of regional financial reports. Meanwhile, good governance has a positive effect on the quality of regional financial reports in the City of Bima.